A CONCEPTUAL FRAMEWORK FOR TEACHING AND ASSESSING CRITICAL THINKING SKILLS IN EFL EDUCATION CLASSROOMS: A SKILL–TASK–EVIDENCE ALIGNMENT MODEL - Li , Zhenglyu; Ganapathy, Malini (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Critical thinking is widely regarded as a key learning outcome in EFL education; however, classroom practice often reveals a misalignment between the teaching of critical thinking and its assessment. Instruction frequently relies on open-ended discussion or task-based activities, while assessment tends to prioritize linguistic accuracy or surface-level responses, limiting insight into learners’ actual development of Critical Thinking Skills (CTSs), particularly in contexts where assessment practices remain predominantly language-focused. To address this issue, this paper proposes a conceptual framework for teaching and assessing critical thinking in English as a Foreign Language (EFL) classroom, termed the Skill–Task–Evidence Alignment Model. Grounded in research on critical thinking, EFL pedagogy, and educational assessment, the model conceptualizes critical thinking as a set of teachable and observable micro-skills and emphasizes alignment among instructional goals, classroom tasks, and assessment evidence. The paper outlines the theoretical rationale and core structure of the model and illustrates its potential application through selected teaching scenarios. Rather than reporting empirical findings, this study presents a theoretically grounded and pedagogically implementable framework intended to inform EFL classroom practice and support future empirical and design-based research.